Signal Transducer and Activator of Transcription-3 Modulation of Cardiac Pathology in Chronic Chagasic Cardiomyopathy - Hoffman, Kristyn A.; Villar, Maria Jose; Poveda, Cristina; Bottazzi, Maria Elena; Hotez, Peter J.; Tweardy, David J.; Jones, Kathryn M. (Frontiers in Cellular and Infection Microbiology, 2021)
Chronic Chagasic cardiomyopathy (CCC) is a severe clinical manifestation that develops in 30%–40% of individuals chronically infected with the protozoal parasite Trypanosoma cruzi and is thus an important public health problem. Parasite persistence during chronic infection drives pathologic changes in the heart, including myocardial inflammation and progressive fibrosis, that contribute to clinical disease. Clinical manifestations of CCC span a range of symptoms, including cardiac arrhythmias, thromboembolic disease, dilated cardiomyopathy, and heart failure. This study aimed to investigate the role of signal transducer and activator of transcription-3 (STAT3) in cardiac pathology in a mouse model of CCC. STAT3 is a known cellular mediator of collagen deposition and fibrosis. Mice were infected with T. cruzi and then treated daily from 70 to 91 days post infection (DPI) with TTI-101, a small molecule inhibitor of STAT3; benznidazole; a combination of benznidazole and TTI-101; or vehicle alone. Cardiac function was evaluated at the beginning and end of treatment by echocardiography. By the end of treatment, STAT3 inhibition with TTI-101 eliminated cardiac fibrosis and fibrosis biomarkers but increased cardiac inflammation; serum levels of interleukin-6 (IL-6), and IFN−γ; cardiac gene expression of STAT1 and nuclear factor-κB (NF-κB); and upregulation of IL-6 and Type I and Type II IFN responses. Concurrently, decreased heart function was measured by echocardiography and myocardial strain. These results indicate that STAT3 plays a critical role in the cardiac inflammatory–fibrotic axis during CCC.